In-Hospital Mortality and Determinants in Patients with Prolonged Total Ischemia Time Undergoing Primary PCI in Nepal - Kadel, Arun; Rauniyar, Binay Kumar; Kharel, Sushant; Neupane, Keshab Raj; Basnet, Abishek; Parajuli, Aryan; Kunwar, Nikosh; Roka, Madhu (Nepalese Heart Journal, 2025)
Background: Prompt recognition and timely performed myocardial reperfusion with primary percutaneous coronary intervention (PCI) in patients with ST-segment elevation myocardial infarction (STEMI) is critical in reducing morbidity and mortality. The aim of our study was to determine the frequency of in-hospital mortality and determinants in patients with prolonged total ischemia time underwent primary PCI at Shahid Gangalal National Heart Centre (SGNHC), Kathmandu. Methods: A cross-sectional analytical study with logistic regression analysis of 111 patient presented with Acute STEMI within a window period of 12 hours and underwent primary PCI at Shahid Gangalal National Heart Centre, Kathmandu, Nepal was conducted. Results: The average age of the patients in the study was 57.05±11.76 years. Frequency of in-hospital mortality in patients with total ischemia time >240 minutes undergoing primary PCI was 8.1%. Risk of in-hospital mortality was higher in 61-80 years of age group and in female patients. Risk of in-hospital mortality was significantly associated with Killip class III and IV, TIMI Risk Score 7-8 and above 8 and 3 vessel disease. In Multivariate analysis, risk of in-hospital mortality was only significantly associated with Killip class III and IV after adjusting the other confounders. Conclusion: The study showed that the frequency of in-hospital mortality in patients with total ischemia time >240 minutes was higher than in patients with total ischemia time ≤ 240 minutes.